versatile toolkit for high throughput functional genomics with Trichoderma reesei - Schuster, André; Bruno, Kenneth S; Collett, James R; Baker, Scott E; Seiboth, Bernhard; Kubicek, Christian P; Schmoll, Monika (Biotechnology for biofuels, 2012)
BACKGROUND: The ascomycete fungus, Trichoderma reesei (anamorph of Hypocrea jecorina), represents a biotechnological workhorse and is currently one of the most proficient cellulase producers. While strain improvement was traditionally accomplished by random mutagenesis, a detailed understanding of cellulase regulation can only be gained using recombinant technologies. RESULTS: Aiming at high efficiency and high throughput methods, we present here a construction kit for gene knock out in T. reesei. We provide a primer database for gene deletion using the pyr4, amdS and hph selection markers. For high throughput generation of gene knock outs, we constructed vectors using yeast mediated recombination and then transformed a T. reesei strain deficient in non-homologous end joining (NHEJ) by spore electroporation. This NHEJ-defect was subsequently removed by crossing of mutants with a sexually competent strain derived from the parental strain, QM9414. CONCLUSIONS: Using this strategy and the materials provided, high throughput gene deletion in T. reesei becomes feasible. Moreover, with the application of sexual development, the NHEJ-defect can be removed efficiently and without the need for additional selection markers. The same advantages apply for the construction of multiple mutants by crossing of strains with different gene deletions, which is now possible with considerably less hands-on time and minimal screening effort compared to a transformation approach. Consequently this toolkit can considerably boost research towards efficient exploitation of the resources of T. reesei for cellulase expression and hence second generation biofuel production.